2021
DOI: 10.3389/fpsyg.2021.676945
|View full text |Cite
|
Sign up to set email alerts
|

Linking Identity Leadership and Team Performance: The Role of Group-Based Pride and Leader Political Skill

Abstract: Recent trends in the leadership literature have promoted a social identity approach of leadership that views leadership as the process of representing, advancing, creating, and embedding a sense of shared identity within a group. However, a few empirical studies explore how and when global identity leadership affects team performance at the workplace. To address this lacuna, we used multi-source and two-wave data among 81 teams to explore the role of group-based pride and leader political skill in the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…[ 51 ] stated that the positive association between identity leadership and group-based pride is stronger when the leader political skill is advanced. Politically skilled leaders can access innumerable evidence and effectively convey influence on followers so that identity leadership has a robust effect on the pride of groups in the team.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ] stated that the positive association between identity leadership and group-based pride is stronger when the leader political skill is advanced. Politically skilled leaders can access innumerable evidence and effectively convey influence on followers so that identity leadership has a robust effect on the pride of groups in the team.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from organizational contexts also suggests that identity leaders can foster a sense of solidarity and pride. In a sample of 81 work teams, Hou et al (2021) found that identity leadership predicted greater team performance by increasing employees’ feelings of pride in their group. Group therapy facilitators may similarly be able to use identity leadership to both (a) construct a hopeful, recovery-oriented group identity that resonates with the reasons that group members decided to attend therapy and (b) increase members’ feelings of solidarity with, and pride in, the therapy group.…”
Section: Proposed Pathways Through Which Identity Leadership Can Faci...mentioning
confidence: 99%
“…In addition, abusive supervision positively affects counterproductive work behavior ( Eschleman et al, 2014 ). Specifically, when a person belongs to and is identified with a certain group, evaluations of group-related events or characteristics will trigger a person’s group emotions ( Hou et al, 2021 ), thereby increasing the incidence of triggering behaviors. Therefore, in an organization, when leaders engage in immoral behaviors such as manipulation and deception toward employees for personal benefit, employees’ perceived leaders’ abusive supervision increases, thus leading to counterproductive work behavior.…”
Section: Introductionmentioning
confidence: 99%